Giant Lipoma of The Breast: Special Clinical Finding - Abdul Hafiz, Muhammad Zaki; Daan khambri; Anandia Putriyuni (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
Lipomas are the most common benign tumors of mesenchymal origin.Lipoma of breast is somewhat difficult to diagnose clinically because of fattyconsistency of breast. Giant lipoma is the mass of lipoma that exceeds atleast 10 cm in one dimension or weighs a minimum of 1000 gr.Only veryfew case reports giant lipoma of the breast available in literature becauserarity in size and location. Due to the fatty composition of the breast,difficulties in diagnosis, threatment, and reconstruction are oftenencountered.Presently, we have reported a case of this rare entity in 49years old female with giant tumor of the left breast that most of its mass,causing breast asymmetry and feel heavy. The operative finding: looks likelipoma between pectoralis major muscle and pectoralis minor muscle witha diameter of 31 cm and weighs 3.1 kg. After excision the tumor we need tomammoplasty.Pathology anatomy examination showed a lipoma.